Determination of carbamate residues in crop samples by cholinesterase-based biosensors and chromatographic techniques - Nunes, G. S.; Skladal, P.; Yamanaka, Hideko [UNESP]; Barcelo, D. (Elsevier B.V., 1998)
An amperometric biosensor based on cholinesterase (ChE) has been used for the determination of selected carbamate insecticides in vegetable samples. The linear range of the biosensor for the N-methylcarbamates (aldicarb, carbaryl, carbofuran, methomyl and propoxur) varied from 5 x 10(-5) to 50 mg kg(-1). Limits of detection were calculated on the basis that the ChE enzymes were 10% inhibited and varied, depending of the combination ChE (as acetyl- or butyrylcholinesterase) vs. inhibitor (pesticide), from 1 x 10(-4) to 3.5 mg kg(-1). The biosensor-based carbamate determination was compared to liquid chromatography/UV methods. Three vegetable samples were spiked with carbofuran and propoxur at 125 mu g kg(-1) followed by conventional procedures. Good correlations were observed for carbofuran in the vegetable extracts (79, 96 and 91% recoveries for potato, carrot and sweet pepper, respectively), whereas for propoxur unsatisfactory results were obtained. Potato and carrot samples were spiked with 10, 50 and 125 mu g kg(-1) carbofuran, followed by direct determination by the amperometric biosensor. The fortified sampler; resulted in very high inhibition values, and recoveries were: 28, 34 and 99% for potato, and 140, 90 and 101% for carrot, respectively, at these three fortification levels. (C) 1998 Elsevier B.V. B.V.
Keywords: carbamates; acetylcholinesterases; crop samples; amperometric biosensors